John Austin Moon papers - Moon, John Austin, 1855-1921.; Appling, Austin M. (Austin Maurice), 1794-
Correspondence, notes, financial records, scrapbooks, and other papers relating chiefly to Moon's service as U.S. representative from Tennessee including his activities as a member of the U.S. House Committee on Post Office and Post Roads. Subjects include legislation concerning parcel post, Tennessee River Valley public works, federal aid in construction of public roads, the Organic Act of Hawaii (1900), and other territorial legislation. Includes material pertaining to Moon's years as a junior member of the law firm of Dodson & Moon, Chattanooga, Tenn.; city attorney, Chattanooga, Tenn.; and Tennessee circuit court judge. Also includes account ledgers of Moon's grandfather Austin M. Appling, merchant of Chattanooga, Tenn., and Bristol, Va.; letters from persons living in Indian Territory in support of legislation sponsored by Moon that would grant statehood to the territory; and newspaper clippings concerning the Tennessee Supreme Court.
Lawyer, jurist, and U.S. representative from Tennessee.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Chattanooga (Tenn.). -- City Attorney; Hawaii; Tennessee. -- Supreme Court; United States. -- Congress. -- House. -- Committee on Post Office and Post Roads; United States. -- Post Office Department; Dodson & Moon; Circuit courts -- Tennessee; Federal aid to transportation; Indians of North America -- Government relations; Law -- United States -- Territories and possessions; Merchants -- Virginia -- Bristol; Parcel post -- United States; Postal service -- United States; Practice of law -- Tennessee -- Chattanooga; Public works -- Tennessee River Valley; Roads -- United States; Bristol (Va.) -- Commerce; Chattanooga (Tenn.) -- Commerce; Indian Territory -- Politics and government; Tennessee -- Politics and government; United States -- Politics and government -- 1865-1933.; United States -- Territories and possessions; Jurists; Lawyers; Representatives, U.S. Congress -- Tennessee